Impact of venous ulcers on patients' quality of life: an integrative review - Fabiana Lopes Joaquim; Rose Mary Costa Rosa Andrade Silva; Maria Paz Garcia-Caro; Francisco Cruz-Quintana; Eliane Ramos Pereira
ABSTRACT Objective: To analyze knowledge gathered about the impact of venous ulcers on patients' quality of life. Method: Systematic bibliographic review study with an integrative approach. Databases of MEDLINE, LILACS, IBECS, CINAHL Complete, Web of Science, Scopus, and CUIDEN Plus were used for selection with the PICOT guiding criteria, through the DeCS and MeSH: adult, aged, varicose ulcer, and quality of life, in Portuguese, Spanish, and English. The inclusion criteria were: full original articles available in the databases selected with adherence to the theme in Portuguese, Spanish, and English, published from 2007 to 2016. Results: The sample included 14 national and international articles with different methodological approaches and investigative contexts, published from 2012 to 2016. Conclusion: Chronic venous ulcers act on patients' bio-psycho-social-spiritual and socioeconomic spheres, having a negative impact on their quality of life.